A novel full length KIR3DL1*0070103 identified by molecular typing. - Yindom, L; Wang, L; Rowland-Jones, S; Dong, T (2013)
KIR3DL1*0070103 differs from KIR3DL1*0070101 with two mutations at 11548 (G>A) and 13889 (T>G), respectively. © 2013 John Wiley and Sons A/S.